In-office tooth bleaching with 38% hydrogen peroxide promotes moderate/severe pulp inflammation and production of ll-1β, TNF-β, GPX, FGF-2 and osteocalcin in rats - Renata Suellen Galvão da Silva-Costa; Andressa Eveline de Lima Ribeiro; Isauremi Vieira de Assunção; Raimundo Fernandes de Araújo Júnior; Aurigena Antunes de Araújo; Gerlane Coelho Bernardo Guerra; Boniek Castillo Dutra Borges (University of São Paulo, 2018)
Abstract Objectives: To study the intensity of inflammatory infiltrate and production of interleukin-1β (ll-1β), tumor necrosis factor-β (TNF-β), fibroblast growth factor-2 (FGF-2), glutathione peroxidase (GPX), and osteocalcin in response to in-office tooth bleaching in rats. Material and Methods: Twenty male Wistar rats were randomized into four groups (n=5) according to the received treatment (tooth bleaching or no treatment - control) and the period of euthanasia after treatment (24 h or 10 days). We performed tooth bleaching using a 38% hydrogen peroxide gel on maxillary and mandibular incisors. After euthanasia, incisors (20 per group) were processed for histological analysis, immunohistochemistry staining of ll-1β, TNF-β, FGF-2 and GPX and osteocalcin by immunofluorescence. We analyzed data using the Mann-Whitney and Kruskal-Wallis/Dunn tests (p<0.05). Results: The bleached groups presented statistically significant differences regarding the pulp inflammation stage compared with the control groups. Bleached teeth showed moderate/severe inflammatory infiltrate and control groups presented absent inflammatory cells or a negligible number of mononuclear cells (p<0.001) at two times (24 h and 10 days). There was strong staining for ll-1β, TNF-β, and GPX in bleached groups at 24 h and strong staining for ll-1β, TNF-β, GPX and FGF-2 at 10 days. After 10 days of tooth bleaching, the bleached group showed a statistically superior amount of osteocalcin than the other groups (p<0.01). Conclusions: Tooth bleaching with 38% hydrogen peroxide causes severe pulp inflammation, but characteristics of tissue repair after 10 days.